Analisis Konteks Situasional pada Podcast Warung Kopi Oleh Has Creative (Kajian Cyberpragmatics) - Amalia Rizki Salsabilah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Advancements in information and communication technology in the era of globalization have significantly transformed human interaction, including through social media and podcast platforms. This study focuses on the analysis of situational context in the "Warung Kopi" Podcast by HAS Creative, aiming to understand how this context influences communication in a digital format. A qualitative approach was used, with an in-depth analysis of the podcast episode featuring Indra Frimawan. Findings reveal that situational context plays a crucial role in message clarification, assertion of speech substance, and the use of small talk and humor. Message clarification and tone modification are effective in enhancing understanding and audience engagement, while techniques such as code-switching and humor add dynamics to the communication. The implications of this study highlight the importance of applying situational context to improve digital communication effectiveness and enrich listener experience. Future research is recommended to explore other aspects of situational context and its variations across different types of podcasts.